2022
DOI: 10.1039/d1ee03028k
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and durable solar thermal energy harvesting via scalable hierarchical coatings inspired by stony corals

Abstract: Stony coral morphology inspires ultra-stable sunlight absorber structure with highest reported absorptance for high-temperature solar thermal applications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Liu et al [15] reported a TiAlON-based nanometer multilayer coatings, whose solar selectivity was 0.936/0.17 with a slight variation of 0.922/0.175 and which was stabilized for 50 h in 550 °C air. Juan F. Torres et al [18] reported Al and Ti-SiO2 coralloid coatings, which exhibited ultrahigh stability after being aged in high-temperature (≥ 800 °C) air for over 2000 h. Beibei Lu et al [9] fabricated a composite coatings of Si3N4, a-Si, Ag, and Cr2O3, which showed no obvious interfacial diffusion after being annealed at 400 °C in air. Hao Wang et al [19] designed a SiO2-Si3N4-W-SiO2-W coatings, which remained stable after being heated for 72 h at 400 °C in air.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [15] reported a TiAlON-based nanometer multilayer coatings, whose solar selectivity was 0.936/0.17 with a slight variation of 0.922/0.175 and which was stabilized for 50 h in 550 °C air. Juan F. Torres et al [18] reported Al and Ti-SiO2 coralloid coatings, which exhibited ultrahigh stability after being aged in high-temperature (≥ 800 °C) air for over 2000 h. Beibei Lu et al [9] fabricated a composite coatings of Si3N4, a-Si, Ag, and Cr2O3, which showed no obvious interfacial diffusion after being annealed at 400 °C in air. Hao Wang et al [19] designed a SiO2-Si3N4-W-SiO2-W coatings, which remained stable after being heated for 72 h at 400 °C in air.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In this approach, photothermal materials, as light harvesters and opticalthermal energy converters, are the key elements. 26 According to previous reports, inorganic materials, such as precious metals 27 and semiconductors, 28,29 and organic materials, such as carbon-based materials 30,31 and conjugated polymers, 32 have been investigated for solar steam generation. However, the extensive application of these new technologies is limited due to the high material costs and complex fabrication procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the P t is unalterable and depends on the local weather, the question becomes how to convert P t to P v as much as possible while suppressing P c and P r . Therefore, high solar to vapor efficiency is significantly related to (1) optimization of the nanophotonic structure to improve photothermal conversion (reduce P r loss) and (2) thermal management to reduce heat conducting to bulk water (reduce P c loss). While much of existing work has focused on either of these two factors, it is necessary to develop integrated evaporators with high light absorption efficiency and low heat loss. In addition, water supply is also important, and efforts have been made in this vein by constructing water transport channels, designing evaporators with a shell layer for evaporation and a core layer for insulation, , and designing hydrogel-substrate-based evaporators. , …”
mentioning
confidence: 99%
“…Because of the synergy of the CuO NSs and C-NPs, the micro/nanostructured C@CuO exhibited over 98.8% light absorption in the ultraviolet band (220–380 nm), over 99.0% in the visible (380–760 nm) band, and over 93.9% in the infrared band (760–2500 nm) across the whole solar spectrum, as Figure d indicates in the red curve. The high light absorption efficiency of C@CuO is favorable for the water evaporation because of the composition synergy and structurally induced multiple internal reflections …”
mentioning
confidence: 99%